Trends in breastfeeding practices and mothers' experience in the French NutriNet-Santé cohort - Frédéric Courtois; Sandrine Péneau; Benoît Salanave; Valentina A. Andreeva; Marie Françoise Roland-Cachera; Mathilde Touvier; Pilar Galan; Serge Hercberg; Léopold K. Fezeu (BMC, 2021)
Abstract Background France has one of the lowest rates in the world regarding breastfeeding initiation and duration. Few studies have explored breastfeeding practices in France since the middle of the twentieth century, or following from initiation to cessation. The purpose of our study was to determine trends in breastfeeding over the past decades regarding public health recommendations, and to examine mothers' perceptions about factors known to have an impact on breastfeeding support and cessation. Methods From the NutriNet-Santé cohort, 29,953 parous women (launched in 2009 to study relation between nutrition and health), were included in the present study. Using web-questionnaires, they were asked retrospectively if they had breastfed their youngest child or not, and if so, the duration of exclusive and total breastfeeding. For those who had breastfed, we investigated their perceptions about support at initiation and during the entire breastfeeding period and reasons for breastfeeding cessation. We also asked those who did not breastfeed about their perceptions and reasons for infant formula feeding their youngest child. Analyses were weighted according to the French census data. Results In the NutriNet-Santé cohort, 67.3% of mothers breastfed their youngest child. The proportion of breastfed children increased over the past few decades, from 55.0% (95% CI 54.3, 55.6) in the 1970s to 82.9% (82.4, 83.4) in the 2010s. Total and exclusive breastfeeding duration went from 3.3 months and 2.4 months respectively in the 1970s to 5.9 months and 3.2 months respectively in the 2010s. Most mothers felt supported at initiation and during the breastfeeding period. A reported desire to have breastfed longer than two months was 59.5%. Mothers who did not breastfeed did it by choice (64.3%). They did not feel guilty (78.2%) and did not perceive a problem not to breastfeed (58.8%), but almost half of them would have liked to have breastfed (45.9%). Conclusion Breastfeeding duration has increased in the past decades but did not reach the public health recommendations threshold. Targets other than mothers have to be considered for breastfeeding education, like the partner and her environment, to increase breastfeeding practices. Trial registration The study was registered at ClinicalTrials.gov ( NCT03335644 ).